2021
DOI: 10.1186/s12891-021-04499-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concurrent repair of medial meniscal posterior root tears during high tibial osteotomy for medial osteoarthritis during short-term follow-up: a systematic review and meta-analysis

Abstract: Background Medial meniscal posterior root tears (MMPRTs) are frequently associated with medial compartment osteoarthritis, leading to loss of meniscal hoop tension. This study aimed to evaluate the efficacy of concurrent MMPRT repair during high tibial osteotomy (HTO) compared to HTO alone in patients with medial osteoarthritis and MMPRTs. Methods The MEDLINE/PubMed, EMBASE, and Cochrane Library databases were searched for studies reporting on conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…Several studies do imply that meniscus root repair might not be required. 19 , 20 , 21 HTO alone were not significantly different when compared with the HTO combine with MMR. Otherwise, we recommend the combined meniscus root repair technique with HTO to enhance anatomic healing of the meniscus root and to decrease the load to the medial knee compartment, thus leading to improved MR repair and halting progressive osteoarthritis of the medial knee compartment.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies do imply that meniscus root repair might not be required. 19 , 20 , 21 HTO alone were not significantly different when compared with the HTO combine with MMR. Otherwise, we recommend the combined meniscus root repair technique with HTO to enhance anatomic healing of the meniscus root and to decrease the load to the medial knee compartment, thus leading to improved MR repair and halting progressive osteoarthritis of the medial knee compartment.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies do imply that meniscus root repair might not be required. [19][20][21] HTO alone were not significantly different when compared with the HTO combine with Use of the transtibial pull-out technique facilitated a precise anatomic attachment of the structure. The Mason Allen suture technique was used for the posterior medial meniscus root stump (Ethibond Sutures USP 2-0, Ethicon), along with Fiber Tape (UltraTape, Smith-Nephew).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the PTS is affected by both the coronal and sagittal planes: on the coronal plane, Samuelsen et al demonstrated that MMPRT can magnify the effect of the increased PTS on ACLR graft forces. 20 ; On the sagittal plane, the varus deformity is an important prognostic factor in meniscal healing and long-term outcomes following MMPRT repair 14 . Therefore, in this study, we choose MMPRT as one of surgical indications of performing slope-reducing osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies indicated that surgical treatment should be recommended to patients with high requirements and no to low-grade osteoarthritis [4,5]. Currently, there are several surgical options for the treatment of meniscus root tears, like meniscectomy, meniscal repair, and meniscus root reconstruction.…”
Section: Introductionmentioning
confidence: 99%